Exortação apostólica Evangelii Gauduim: características, origens e impactos na Igreja Católica - Santos, José Genilton Costa dos (2024)
This Dissertation seeks to understand the transformations within the Catholic Church with the Papacy of Francis, the first Jesuit and Latin American pope in the millennial history of the Catholic Church. It starts from the premise that Pope Francis, a supporter of the Theology of the People during his pastoral life in Argentina, has taken the theological and pastoral positions of this theology to the government of the Church, through the Apostolic Exhortation Evangelii Gaudium - EG. Thus, this study aims to critically analyze this Exhortation, written by Pope Francis and published in 2013, seeking to understand the characteristics of this Catholic document, examining the origins of the document and analyzing the impacts of the document, both within the Catholic Church and in society, specifically the Brazilian one. The first chapter presents the characteristics of Evangelii Gaudium - EG, the Magisterium of Pope Francis, his theological and pastoral line of thought and the influences of the Latin American locus, especially Argentina, where he was born, grew up and received a Jesuit formation. . It focuses on his trajectory as a priest and Cardinal of Argentina, emphasizing his pastoral experience in the outskirts of Buenos Aires and the social, political and economic context. The second chapter focuses its analysis on the origins of the document Evangelii Gaudium - EG, seeking to place it in the Magisterium of Pope Francis, as well as the themes present in the EG that signal influences from documents after the Second Vatican Council, documents after Latin American and Caribbean Conferences. The third chapter analyzes the impacts of the document on the actions of the Catholic Church. Basically, we seek to understand how the Church, in the world and in Brazil, has been impacted over the last ten years by the guidelines presented in E G. This research adopts the methodology of bibliographical research as the main research tool. It can be seen, in the analysis of the document, that the paths proposed by Pope Francis for governing the Church reveal that the personal trajectory and theological positions of the Jesuit Jorge Mario Bergoglio intersect and are present in the teachings and actions of the current pope.